Evidence for non-Andersonian faulting above evaporites in the Nile Delta - Tingay, Mark; Bentham, P.; De Feyter, A.; Kellner, A. (Geological Society Publishing House, 2012)
This study examines present-day stress orientations from borehole breakout and drilling-induced fractures in 57 boreholes in the Nile Delta. A total of 588 breakouts and 68 drilling-induced fractures from 50 wells reveal sharply contrasting present-day maximum horizontal stress (SHmax) orientations across the Nile Delta. A typical deltaic margin-parallel SHmax exists in parts of the Nile Delta that are below or absent from evaporites (NNE-SSW in the west, east- west in the central Nile, ESE-WNWin the east). However, a largely margin-normal (NNE-SSW) SHmax is observed in sequences underlain by evaporites in the eastern Nile Delta. The marginnormal supra-salt SHmax orientations are often subperpendicular to the strike of nearby active extensional faults, rather than being parallel to the faults as predicted by Andersonian criteria. The high angle between SHmax and strike of these extensional faults represents a new type of non-Andersonian faulting that is even less-suitably oriented for shear failure than previously described anomalous faulting such as low-angle normal faults and highly oblique strike-slip faults (e.g. San Andreas). While the mechanics of these non-Andersonian faults remains uncertain, it is suggested that the margin-normal supra-salt orientation generated by basal forces imparted upon rafted blocks sliding down seawards-dipping evaporites.